AR+G Atividade Educacionais: um aplicativo de realidade aumentada com gamification para auxiliar no processo ensino-aprendizagem de alunos com deficiência mental - Colpani, Rogério (Universidade Federal de São Carlos, 2015)
In this work, it developed an Augmented Reality with Gamification application to assist the learning process of students with intellectual disabilities in general. This application enables the teacher explore various skills with students, how examples, classification, discrimination, color, quantity, problem situations, functionally of objects and association. It was evaluated by two special education professionals and tested by ten students with intellectual disability. In order to evaluate the potential of the application was used quantitative and qualitative methods. In the quantitative stage, questionnaire were applied to the teacher. This questionnaire, regarding the skills presented by the students, were applied prior to the tests with the application get started in schools and were reapplied after a period of two months of tests. For the statistical analysis, it was used the t-test for hypothesis testing and descriptive statistics to organize, summarize and present the data. In the qualitative stage, was evaluated the technical and pedagogical usability of the application in order to the views of experts in the area, making use of questionnaire and observational technical, your opinions about the ease of learning and satisfaction of the application use. The results show that the AR+G Educational Activities contributes to the improvement of skills that, the traditional teaching methods used so far by students that had not been seized by them in a conventional way. It is an easy to learn tool and provides satisfaction from potential users during use. As for learning material, it provides individual knowledge construction facility or collective, presents evidence of engagement and motivation of the students while conducting their activities, as well as more active behavior of the same.
AR+G Educational Activities: an argumented reality with gamification application to assit ther learning process of studentes with intellectual disabilities
Keywords: realidade aumentada; gamification; deficiência intelectual; software de aplicação; educação especial - ensino auxiliado por computador; aprendizagem; augmented reality; gamification; intellectual disabilities; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO